Modernization of Technical Units of the Nepali Army for Mission Success (A Mixed Methods Exploratory Research) - Bastola, Dipak Prasad (Unity Journal, 2024)
In this research paper, the author has tried to establish the historical journey of technical units and their organizational changes, especially in the field of modernization in the Nepali army. A brief historical background of such technical units is also one of the areas of interest of the researcher to enhance the research questions. A mixed method has been applied. An exploratory approach has been used to answer the research questions. Almost 10 army experts, including defense security experts who know the Nepali army closely participated in the Delphi technique, based on interview questionnaires to explore the research findings. Secondary data have been used for the quantitative research analysis and 10 veteran Generals participated in qualitative research. In quantitative analysis, the growth and strength were analyzed. Medical, Aviation, EME, Civil Engineering, and Production Units were chosen for the study. Triangulation of methods was used to establish the reliability and credibility of the research findings. The results show that top leadership of the Nepali Army is one of the top factors for the modernization of Technical Units than any other factors and the Mission factor comes in the second position that is the serendipity of these research findings. The study also revealed that without a perfect balance between technology and technocrats, mission success is difficult to achieve. This research has answered all the research questions and has given enough avenues for the modernization process of technical units of the Nepali Army in the upcoming days to achieve organizational, as well as mission success of the Nepali Army.